Conceptual model of wearable persuasive multimedia for controllability awareness toward mental health issue / Umi Hanim Mazlan … [et al.] - Mazlan, Umi Hanim; Sarif, Siti Mahfuzah; Abdul Salam, Sobihatun Nur; Faisal Mohamed, Nur Fadziana; Ibrahim, Maznah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
Mental health issues among students have been an alarming problem in recent years. The issues become more worrying during and after the post-pandemic Covid-19. Besides the help and treatment from a professional physician, technology can also act as an early prevention tool to ensure one's controllability awareness is always controllable to prevent mental disorders like depression from getting worse. For example, the sensor embedded in wearable technology like a smartwatch can be utilized to detect input such as heart rate to determine the possibility of depression. In addition, the integration of the other two powerful technology, persuasive and multimedia, is a value-added to influence users in managing their mental health. Moreover, proper consolidation of technologies could increase the effectiveness of the system. However, there is no empirical evidence yet that integrating those technologies, especially in enhancing controllability awareness regarding a mental health problem. Therefore, this study is proposing a conceptual design model that integrates the wearable, persuasive and multimedia principles for application development in wearable platform. The constructed design model is intended to provide the developer with a guide to build solutions to enhance awareness, particularly controllability awareness toward mental health issues.